Are we thinking critically about critical thinking? Uncovering uncertainties in internationalised higher education. (March 2021) - Liyanage, Indika; Walker, Tony; Shokouhi, Hossein
Abstract: There are widespread expectations that critical thinking (CT) be a core learning and attribute of graduates in higher education (HE). Academic teaching staff ostensibly embed discipline specific CT in HE program and course objectives, in teaching and learning experiences including assessment, and routinely make judgements about the CT skills of students. It is curious then that routinely contested assumptions about the CT capacities of whole cohorts of students made on the bases of ethnic and sociocultural backgrounds continue to escape more rigorous scrutiny in practice in HE classrooms. We use reflections of a group of academic advisors who work with local and international students at a large university in Australia to uncover uncertainties about CT in HE and the need for more nuanced approaches to the strengths and needs of students irrespective of being members of reductive cohorts. We propose, in fact, that in order to ensure that all students have opportunities to develop CT skills and demonstrate them effectively in line with local expectations, critical attention be directed to generalised assumptions based on cultural affiliations.